E-Book Interaktif Terintegrasi Kearifan Lokal Karawitan sebagai Bahan Ajar Kontekstual IPA SMP: Analisis Konten - Rika Nuryani Suwarno; Rahmatullah Rahmatullah (Indonesian, 2021)
Some of the competencies needed by participants in this 21st century era such as critical thinking, scientific culture, and making the right decisions to solve students' problems in everyday life. The competence of students in Indonesia is still low and needs to be improved. Therefore, alternative solutions that can be used are interactive e-books as contextual teaching materials. This literature review and content analysis aims to provide an interactive e-book description of local wisdom on how to motivate and help students to facilitate students in learning science so that they are able to achieve the expected competencies. Data collected by observing text books and articles of previous research. Search articles with the help of Google software, research gate, and so on. The results obtained that the e-book integrated with local wisdom of karawitan has a positive impact. An interactive e-book of local musical wisdom that is interesting and according to its content provides students with a meaningful learning experience because students can learn on their own. So it can be said that interactive e-books can be integrated with local wisdom of karawitan as contextual teaching materials for junior high school science.